Sustainable castor oil-derived cross-linked poly(ester-urethane) elastomeric films for stretchable transparent conductive electrodes and heaters - Laukkanen, Timo; Reddy Pulikanti, Guruprasad; Barua, Amit; Kumar, Manish; Kolpakov, Kristofer; Tirri, Teija; Sharma, Vipul (Royal Society of Chemistry (RSC), 2025)
Substrates are essential for flexible and stretchable devices, requiring sustainability, stretchability, transparency, thermal stability, and chemical stability. This study introduces a sustainable cross-linked poly(castor oil-co-δ-valerolactone)cyclohexyl urethane (PCVU) substrate for flexible, stretchable transparent conducting electrodes (TCEs) based strain sensors and heaters. PCVU is synthesized as a highly transparent (>90%), stretchable (>190%), and thermally stable (∼210 °C) substrate via thermal cross-link polymerization of poly(castor oil-co-δ-valerolactone)triol and 4,4′-methylenebis(cyclohexyl isocyanate) on a glass mold. PCVU exhibits high chemical stability in various organic solvents and good degradability in acidic (pH 0, 45% degradation), alkaline (pH 14, 100% degradation), and phosphate buffer (pH 7.2, 9% degradation) aqueous solutions over 150 days. Using PCVU, we fabricated a robust, flexible, and stretchable TCE with low sheet resistance (<50 Ω sq−1). The TCE fabrication process involves applying an electrospun polyvinyl alcohol (PVA) layer as a temporary wet film leveling agent to improve the dispersion and adhesion of silver nanowires (AgNWs) on PCVU films, followed by a heat-based nano-welding technique to enhance the durability and mechanical stability of the TCE. The TCE-based strain sensor showed stable and repeatable resistance changes (ΔR/R0) under 5–15% strains, with fast response and consistent signal stability over 100 cycles at 5% strain. The flexible heater reached a maximum average temperature of ∼150 °C at 5.5 V, with rapid heating and cooling responses (15 s each). Practical applications include a strain sensor for real-time monitoring of human motion (finger, wrist, elbow, and neck flexion) and a heater used as a thermotherapy pad for the wrist and finger, demonstrating the potential of PCVU-based TCEs for wearable and medical devices.